Learn How To Convert Postfix To Infix Notation using Stack in C Programming Language. The Postfix notation is also known as **Reverse Polish Notation.** Before you proceed further with this code, you must know the complete operations of **stack data structure**.

#### Postfix To Infix Conversion Example

**Postfix String: 66+**

**Infix String: 6 + 6**

#### Algorithm To Convert Postfix Expression into Infix Notation

- Scan the Postfix String from Left to Right.
- If the character is an Operand, then Push it on to the Stack.
- If the character is an Operator, then Pop Operator 1 and Operand 2 and concatenate them using Infix notation where the Operator is in between the Two Operands.
- The resultant expression is then pushed on the Stack
- Repeat the above steps till the Postfix string is not scanned completely.
- Use parantheses properly to ensure correct order for evaluating the final expression.

#### C Program For Postfix To Infix Conversion using Stack Data Structure

#include<stdio.h> #include<stdlib.h> #include<string.h> # define MAX 20 char str[MAX], stack[MAX]; int top = -1; char pop() { return stack[top--]; } void push(char ch) { stack[++top] = ch; } void postfix_to_infix(char expression[]) { int count, length; char element, operator; length = strlen(expression); for(count = 0; count < MAX; count++) { stack[count] = 0; } printf("\nInfix Expression:\t"); printf("%c", expression[0]); for(count = 1; count < length; count++) { if(expression[count] == '-' || expression[count] == '/' || expression[count] == '*'|| expression[count] == '+') { element = pop(); operator = expression[count]; printf(" %c %c", operator, element); } else { push(expression[count]); } } printf("%c", expression[top--]); } int main() { char postfix_expression[50]; printf("\nEnter Postfix Expression:\t"); scanf("%s", postfix_expression); postfix_to_infix(postfix_expression); printf("\n"); return 0; }

#### Output

In case you get any compilation errors or any doubts in this C Program For Conversion of Postfix Expression into Infix Expression, let us know about it in the Comment Section below.

I have detected a bug in your code if i input let’s say the expression xy-z-uv+/ the infix that i am getting is x-y-z+v/u which is wrong the correct infix is (x-y-z)/(u+v)